Equivalent stress-strain model of half grouted sleeve connection under monotonic and repeated loads: Experiment and preliminary application. (1st June 2022) - Zhang, Xue; Zhao, Yuheng; Guo, Yufeng; Li, Zhengyao
Highlights: The load-deformation behaviors of HGSC are tested under monotonic and repeated loads. The effect of rebar diameter, as well as the spliced length of rebar in the sleeve is discussed. The bond-slip mechanism of spliced rebar in sleeve is revealed with pre-installed gauges. The equivalent stress-strain models are proposed and preliminarily verified for HGSC under monotonic and repeated loads. Abstract: The half grouted sleeve connection (HGSC) is widely adopted in the construction of precast concrete (PC) structures. So far, a few studies have been developed on the mechanical behavior of HGSC, however, efficient load-deformation models of HGSC are still scarce, which limits the numerical analysis of PC structures. In this study, therefore, an experimental study is undertaken to propose equivalent stress-strain models of HGSC under monotonic and repeated loads. The effect of rebar diameter, as well as the spliced length of rebar in the sleeve on the load-deformation behavior of HGSC is investigated with 60 specimens. Based on the test results, the failure mode, load capacity and strain of the spliced rebar is discussed. The results show that the failure mode of HGSC is mainly related to the spliced length of rebar. The capacity of HGSC is affected by the failure mode rather than the loading type. Moreover, a non-uniform distribution of bond stress of the spliced rebar is observed from the measured strains in the rebar. Finally, equivalent stress-strain models are proposed for the HGSC under monotonic and repeated loads. The model is established by revising the bi-linear stress-strain model of bare rebar, thus can be applied in the numerical study of PC members with high computational efficiency. The parameters of the models are calibrated with the test data obtained in the current study. A numerical simulation of a PC column with HGSC is developed to preliminarily verify the proposed model. The results show that the prediction of member deformation can be greatly improved by using the proposed model.